2022
DOI: 10.1111/iju.14826
|View full text |Cite
|
Sign up to set email alerts
|

Limited impact of erectile function on health‐related quality of life in Japanese men undergoing robot‐assisted radical prostatectomy

Abstract: To investigate the impact of erectile function on health-related quality of life in Japanese prostate cancer patients following robot-assisted radical prostatectomy. Methods: Time-dependent changes in erectile function and health-related quality of life were assessed using the erection hardness score and Medical Outcomes Study 8-Item Short Form Health Survey, respectively, in 229 consecutive Japanese patients undergoing robot-assisted radical prostatectomy. In this series, patients with erection hardness score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Namiki et al showed that Japanese men were more likely to have poor sexual function, including sexual desire, erection ability, erection quality, and intercourse, than American men (19). Therefore, in the present study, EF was evaluated with EHS because it may be more appropriate than other tools, such as the International Index of Erectile Function-5, for men with an inactive sexual health status, such as Japanese men, as previously reported (20). In this series, no significant differences were noted between EHS before and 6 months after HoLEP.…”
Section: Discussionmentioning
confidence: 67%
“…Namiki et al showed that Japanese men were more likely to have poor sexual function, including sexual desire, erection ability, erection quality, and intercourse, than American men (19). Therefore, in the present study, EF was evaluated with EHS because it may be more appropriate than other tools, such as the International Index of Erectile Function-5, for men with an inactive sexual health status, such as Japanese men, as previously reported (20). In this series, no significant differences were noted between EHS before and 6 months after HoLEP.…”
Section: Discussionmentioning
confidence: 67%
“…The low frequency of sexual intercourse among Japanese couples is a well‐known fact, and there are limited impacts on sexual dysfunction if expressed as a mean 28,29 . On the other hand, a number of patients need sexual care, and strong, albeit limited, sexual concerns have been found in men with high sexual activity 10 .…”
Section: Current Situation Of Sexual Medicine For Prostate Cancer Pat...mentioning
confidence: 99%
“…The low frequency of sexual intercourse among Japanese couples is a well-known fact, and there are limited impacts on sexual dysfunction if expressed as a mean. 28,29 On the other hand, a number of patients need sexual care, and strong, albeit limited, sexual concerns have been found in men with high sexual activity. 10 Unsatisfied patients in the high-interest group demonstrated significantly deteriorated sexual health at 6 and 12 months after surgery despite relatively good recovery of sexual function.…”
Section: Current Situation Of Sexual Medicine For Prostate Cancer Pat...mentioning
confidence: 99%
“…Tamura et al reported that erectile function has a limited impact on postoperative health-related quality of life in Japanese patients with robot-assisted radical prostatectomy (RARP). 1 Of course, in Japanese prostate cancer patients, erectile function is very important and plays an important role in treatment decisions, and efforts must be made to deal with the altered physical condition. 2 On the other hand, it has been reported that fewer middleaged Japanese men have regular sexual intercourse than men of other races or cultures.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Tamura et al . reported that erectile function has a limited impact on postoperative health‐related quality of life in Japanese patients with robot‐assisted radical prostatectomy (RARP) 1 …”
mentioning
confidence: 99%